Regional manifestation of the widespread disruption of soil-landscapes by the 4kyr BP impact-linked dust event using pedo-sedimentary micro-fabrics - Courty, M.; Crisci, A.; Fedoroff, M.; Grice, Kliti; Greenwood, Paul; Mermoux, M.; Smith, D.; Thiemens, M. (Springer Verlag, 2008)
The co-occurrence of a sharp dust peak, low lake levels, forest reduction, and ice retreat at ca. 4-kyr BP throughout tropical Africa and West Asia have been widely explained as the effect of an abrupt climate change. The detailed study of soils and archaeological records provided evidence to re-interpret the 4 kyr BP dust event linked rather to the fallback of an impact-ejecta, but not climate change. Here we aim to further investigate the exceptional perturbation of the soil-landscapes widely initiated by the 4 kyr BP dust event. Results are based on soil data from the eastern Khabur basin (North-East Syria), the Vera Basin (Spain), and the lower Moche Valley (West Peru) compared with a new study at the reference site of Ebeon (West France). The quality of the 4 kyr BP dust signal and the related environmental records are investigated through a micromorphological study of pedo-sedimentary micro-fabrics combined with SEM-microprobe, mineralogical, and geochemical analyses.In the four regions studied, the intact 4 kyr BP signal is identifi ed as a discontinuous burnt soil surface with an exotic dust assemblage assigned to the distal fallout of an impact-ejecta. Its unusual two-fold micro-facies is interpreted as (1) flash heating due to pulverization of the hot ejecta cloud at the soil surface, and (2) high energy deflation caused by the impact-related air blast. Disruption of the soil surface is shown to have been rapidly followed by a major de-stabilisation of the soil cover. Local factors and regional settings have exerted a major control on the timing, duration, and magnitude of landscape disturbances. Studies showed how a high quality signal allows to discriminate the short-term severe landscape disturbances linked to the exceptional 4 kyr BP dust event from more gradual environmental changes triggered by climate shift at the same time.